The new infrared diffuse interstellar bands in the Galactic center. Issue Volume 9:Issue S303(2013) (22nd May 2014) - Geballe, T. R.; Najarro, F.; de la Fuente, D.; Figer, D. F.; Adamson, A. J.; Rawlings, M. G.
Abstract : The diffuse interstellar bands (DIBs) are a set of absorption features, some of which are broad ("diffuse"), that are formed in the diffuse ISM. Since their discovery nearly a century ago their numbers have increased to over 500. The strongest of these are known to be ubiquitous in the universe. There is general consensus that they are produced by large carbon-bearing molecules; however, no specific identification of any single DIB has survived scrutiny. The overwhelming majority of DIBs are at optical and very near infrared wavelengths. In 1990 two DIBs were identified in J -band spectra, at 1.18 μm and 1.31 μm by Joblin et al . (1990); until recently these were the longest wavelength examples known.